Theoretical and Methodological Approaches to the Formation of Prices of Company Теоретико-методические подходы к формированию цены предприятия - Timofeev Vladimir N.; Mardus Natalya Yu. (Problemi Ekonomiki, 2012)
The article deals with the theoretical and methodological principles for the price formation during the period of market relations. Theoretical and methodological basis of the study served as the theory of marketing and scientific methods of scientific knowledge. In order to justify the high level of scientific accuracy to the definition of the strategy and tactics of pricing has been investigated the concept of "price policy", "pricing strategy" and "pricing tactics" as the result revealed differences in some of these concepts by scientists of the field of research, which suggests a certain ambiguity about in the interpretation of certain concepts. An association between has been established these concepts. Supporting the claim that the price strategy is a means of achieving competitive strategies of the company, and pricing is an element of marketing. In addition, for effective pricing there is a need to introduce a systematic approach, which is a well-structured scheme of the formation of the strategy and tactics of pricing in marketing with certain components of the system, the interrelation and the logical sequence of which may be the key of successful result in the formation of pricing mechanism in the system of strategic marketing. Requested to carry out the practical pricing activities of modern enterprises with marketing point. В статье рассмотрены теоретические и методологические положения стратегического формирования цены в период рыночных отношений. С целью обоснования высокого уровня научной точности в определении стратегии и тактики ценообразования, были исследованы понятия «ценовая политика», «ценовая стратегия» и «ценовая тактика», в результате чего были выявлены различия в определении данных понятий, что позволяет говорить об определенной неоднозначности в их толковании. Была установлена взаимосвязь между данными понятиями. Подтверждается, что ценовые стратегии являются средством достижения конкурентных стратегий фирмы, а ценообразование представляет собой элемент маркетинга. Кроме того, для эффективного ценообразования существует необходимость применения системного подхода, который представляет собой четко структурированную схему процесса формирования стратегии и тактики ценообразования в маркетинге с отдельно установленными компонентами системы, взаимосвязь и логическая последовательность которых может стать залогом успешного результата в формировании механизма ценообразования в системе стратегического маркетинга. Предложено осуществлять практическое ценообразование в деятельности современных предприятий с позиции маркетинга.